Hybrid palladium-ceria nanorod electrocatalysts applications in oxygen reduction and ethanol oxidation reactions in alkaline media. (26th April 2021) - Pinheiro, Victor S.; Souza, Felipe M.; Gentil, Tuani C.; Parreira, Luanna S.; Batista, Bruno L.; Santos, Mauro C.
Abstract: Fossil fuel alternatives are being increasingly studied, and alkaline direct ethanol fuel cells (ADEFC) have acquired importance, as to ethanol is a renewable fuel. In this context, the aims of the present study were to synthesize, characterize and evaluate electrocatalytic activity in oxygen reduction reaction (ORR) and ethanol oxidation reaction (EOR) using hybrid electrocatalysts based on Pd nanoparticles and CeO2 nanorods supported on carbon black for application in ADEFC. The highest OCV, maximum current and power densities obtained using Pd15 (CeO2 NR)10 (Vn)75 as the cathode and Pd10 (CeO2 NR)20 (Vn)70 as the anode were 1270 mV, 190 mA cm −2 and 65 mW cm −2, respectively. These interesting results are justified by the highest ID /IG ratio and ECSA, which suggest a high number of oxygenated species, defects and vacancies in these electrocatalysts and by the synergistic effect between CeO2 NR and Pd nanoparticles. Therefore, these hybrid electrocatalysts are promising for ADEFC applications. Graphical abstract: Image 1 Highlights: Hybrid electrocatalysts based on Pd and Ceria nanorods for EOR and ORR. The electrocatalysts were applied as cathode and anode in ADEFC experiments. Better performance compared to commercial materials in ADEFC tests. Oxygenated species, vacancies and defects are the main electrocatalytic effects.